„ … daß Ihre dienstlichen Funktionen beim hiesigen Hoftheater durch dieses Nebenamt keinerlei Beeinträchtigung erleiden“ – Künstler des Königlichen Hoftheaters als Lehrende am Konservatorium - Tumat, Antje (150 Jahre Staatliche Hochschule für Musik und Darstellende Kunst Stuttgart)

Wissen zwischen Lokalisierung und Globalisierung - Spiegel, Anna (Handbuch Wissenssoziologie und Wissensforschung)
Keywords: Wissenssoziologie

Verbstellung in frühen Phasen des kindlichen Grammatikerwerbs und beim Dysgrammatismus als Symptombereich spezifischer Sprachentwicklungsstörungen - Grosser, Christine

Probing the extent of the Sr2+ ion condensation to anionic polyacrylate coils: A quantitative anomalous small-angle x-ray scattering study - Goerigk, G.; Huber, Klaus; Schweins, R. (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Temperature-Induced Collapse of Alkaline Earth Cation−Polyacrylate Anion Complexes - Lages, Sebastian; Schweins, Ralf; Huber, Klaus (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Trapping Metal-Organic Framework Nanocrystals: An in-Situ Time-Resolved Light Scattering Study on the Crystal Growth of MOF-5 in Solution - Hermes, Stephan; Witte, Thomas; Hikov, Todor; Zacher, Denise; Bahnmüller, Stefan; Langstein, Gerhard; Huber, Klaus; Fischer, Roland A. (Journal of the American Chemical Society)
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Structure−Property Relationship in Stimulus-Responsive Bolaamphiphile Hydrogels - Meister, Annette; Bastrop, Martin; Koschoreck, Sven; Garamus, Vasil M.; Sinemus, Thomas; Hempel, Günter; Drescher, Simon; Dobner, Bodo; Richtering, Walter; Huber, Klaus; Blume, Alfred (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Controlled Formation of Ag Nanoparticles by Means of Long-Chain Sodium Polyacrylates in Dilute Solution - Huber, Klaus; Witte, Thomas; Hollmann, Jutta; Keuker-Baumann, Susanne (Journal of the American Chemical Society)
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Time resolved structure analysis of growing β-amyloid fibers - WITTE, T; HALLER, L; LUTTMANN, E; KRUGER, J; FELS, G; Huber, Klaus (Journal of Structural Biology)
Keywords: Structural Biology

Informational Capitalism and the Digital Divide in Africa. (Proceedings of the Conference “Cyberspace 2006“, 24.11-25.11.2006, Masaryk University, Brno, Czech Republic) - Fuchs, Christian; Horak, Eva (Masaryk University Journal of Law and Technology)

2006 Fuschl design conversation: Fuschl extension team report: igniting a new form of design conversation - Fuchs, Christian; Horiuchi, Yoshihide; Kordes, Urban; Rivera, Barbara; Rowland, Gordon; Walton, Doug (The Research Reports of Shibaura Institute of Technology, Social Sciences and Humanities)

Transnational space and the “network society“ - Fuchs, Christian (21st Century Society. The journal’s name has since 2011 been Contemporary Social Science: Journal of the Academy of Social Sciences)

A Dynamic Systems View of Economic and Political Theory - Fuchs, Christian; Collier, John (Theoria: A Journal of Social and Political Theory 113 (August 2007))

Mesoporous CeO2: Synthesis by nanocasting, characterisation and catalytic properties - Roggenbuck, Jan; Schäfer, Hanno; Tsoncheva, Tanya; Minchev, Christo; Hanss, Jan; Tiemann, Michael (Microporous and Mesoporous Materials)
Mesoporous CeO2 was synthesised by using CMK-3 carbon as a structure matrix. Nitrogen physisorption, powder X-ray diffraction, transmission electron microscopy (TEM), selected-area electron diffraction (SAED), energy-dispersive X-ray (EDX), X-ray absorption near-edge structure (XANES), and thermal (TG/MS) analysis were used for their characterisation. Methanol decomposition to hydrogen, CO, and methane was used as a catalytic test reaction. The obtained products exhibit uniform pores with a diameter of ca. 5 nm in a two-dimensional hexagonal periodic arrangement, as well as interparticle porosity, broadly distributed around ca. 35 nm; the specific surface area is 148 m2 g−1. The pore walls are polycrystalline. The polycrystalline nature and high surface-to-volume ratio of the products is reflected in an increased signal intensity in X-ray absorption spectroscopy. The synthesis of CeO2 from Ce(NO3)3 within the pores of the carbon matrix and the subsequent thermal combustion of the carbon is monitored by thermal analysis. Catalytic tests reveal that the activity of the mesoporous products in methanol decomposition are substantially higher than for a non-porous sample.

Crystalline ZnO with an enhanced surface area obtained by nanocasting - Waitz, T.; Tiemann, Michael; Klar, P. J.; Sann, J.; Stehr, J.; Meyer, B. K. (Applied Physics Letters)
The authors report the synthesis of nanoporous ZnO, which exhibits a periodically ordered, uniform pore system with crystalline pore walls. The crystalline structure is investigated by x-ray diffraction, transmission electron microscopy, and selected area electron diffraction. The large specific surface area and the uniformity of the pore system are confirmed by nitrogen physisorption. Raman spectroscopy along with low-temperature photoluminescence measurements confirms the high degree of crystallinity and gives insight into defects participating in the radiative recombination processes. The authors thank Günter Koch for recording the TEM images and Marie-Luise Wolff for valuable help in the laboratory one of the authors (M.T.) thanks Michael Fröba for the continuous support.

In-situ X-ray diffraction study on the formation of a periodic mesoporous organosilica material - Tiemann, Michael; Teixeira, Cilâine V.; Cornelius, Maximilian; Morell, Jürgen; Amenitsch, Heinz; Lindén, Mika; Fröba, Michael (Recent Progress in Mesostructured Materials - Proceedings of the 5th International Mesostructured Materials Symposium (IMMS2006), Shanghai, P.R. China, August 5-7, 2006)
In-situ X-ray diffraction study on the formation of a periodic mesoporous organosilica material...

Ordered mesoporous ZnO for gas sensing - Wagner, T.; Waitz, T.; Roggenbuck, J.; Fröba, M.; Kohl, C.-D.; Tiemann, Michael (Thin Solid Films)
We report on the synthesis and the gas-sensing properties (CO and NO2 detection) of mesoporous zinc oxide. A two-step structure replication method for the synthesis is employed. In the first step mesoporous SBA-15 silica is prepared by the utilization of self-organization of amphiphilic organic agents. This mesoporous silica is used as the structure matrix for synthesizing mesoporous carbon CMK-3, which, in turn, is employed for yet another replication step, using zinc nitrate as the precursor. The resulting material is characterized by X-ray diffraction and nitrogen physisorption and its gas-sensing properties are compared with a non-porous ZnO sample.

Porous Metal Oxides as Gas Sensors - Tiemann, Michael (Chemistry - A European Journal)
Semiconducting metal oxides are frequently used as gas-sensing materials. Apart from large surface-to-volume ratios, well-defined and uniform pore structures are particularly desired for improved sensing performance. This article addresses the role of some key structural aspects in porous gas sensors, such as grain size and agglomeration, pore size or crack-free film morphology. New synthesis concepts, for example, the utilisation of rigid matrices for structure replication, allow to control these parameters independently, providing the opportunity to create self-diagnostic sensors with enhanced sensitivity and reproducible selectivity.

Gas-sensing properties of ordered mesoporous Co3O4 synthesized by replication of SBA-15 silica - Wagner, Thorsten; Roggenbuck, Jan; Kohl, Claus-Dieter; Fröba, Michael; Tiemann, Michael (Recent Progress in Mesostructured Materials - Proceedings of the 5th International Mesostructured Materials Symposium (IMMS2006), Shanghai, P.R. China, August 5-7, 2006)
Gas-sensing properties of ordered mesoporous Co3O4 synthesized by replication of SBA-15 silica...

Any-World Access to OWL from Prolog - Matzner, Tobias; Hitzler, Pascal (Proceedings of the 30th Annual German Conference on Artificial Intelligence. Osnabrück, Germany)